2022
DOI: 10.3389/ftox.2022.826488
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Neurotoxicity Testing: Novel Applications in the Adverse Outcome Pathway Framework

Abstract: Neurological hazard assessment of industrial and pesticidal chemicals demands a substantial amount of time and resources. Caenorhabditis elegans is an established model organism in developmental biology and neuroscience. It presents an ideal test system with relatively fewer neurons (302 in hermaphrodites) versus higher-order species, a transparent body, short lifespan, making it easier to perform neurotoxic assessment in a time and cost-effective manner. Yet, no regulatory testing guidelines have been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…To confirm that the mobility phenotype observed in the fem-1 mutants is due to synaptic defects, we examined the rate of worm paralysis in response to aldicarb and levamisole. Acetylcholine (Ach) is necessary for the transmission of an action potential between neurons, and it exerts its action by binding to nicotinic (nAchR) and muscarinic Ach receptors (Sammi et al, 2022; Spensley et al, 2018). Synaptic acetylcholinesterase (AchE) manages neuromuscular transmission by catabolizing Ach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm that the mobility phenotype observed in the fem-1 mutants is due to synaptic defects, we examined the rate of worm paralysis in response to aldicarb and levamisole. Acetylcholine (Ach) is necessary for the transmission of an action potential between neurons, and it exerts its action by binding to nicotinic (nAchR) and muscarinic Ach receptors (Sammi et al, 2022; Spensley et al, 2018). Synaptic acetylcholinesterase (AchE) manages neuromuscular transmission by catabolizing Ach.…”
Section: Resultsmentioning
confidence: 99%
“…1D). However, in the aldicarb assay, a higher percentage of paralyzed worms at a given time indicates a higher general Ach neurotransmission, whereas the levamisole test selectively evaluates nAchR activity (Mahoney et al, 2006; Miller et al, 1996; Sammi et al, 2022). We found that the fem-1 mutants were significantly (p<0.001) more sensitive to aldicarb but not to levamisole (p=0.34) compared to wild-type worms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that the mobility phenotype observed in the fem-1 mutants is due to synaptic defects, we examined the rate of worm paralysis in response to aldicarb and levamisole. Acetylcholine (Ach) is necessary for the transmission of an action potential between neurons, and it exerts its action by binding to nicotinic (nAchR) and muscarinic Ach receptors ( 32 , 33 ). Synaptic acetylcholinesterase (AchE) manages neuromuscular transmission by catabolizing Ach.…”
Section: Resultsmentioning
confidence: 99%
“…S1D ). However, in the aldicarb assay, a higher percentage of paralyzed worms at a given time indicates a higher general Ach neurotransmission, whereas the levamisole test selectively evaluates nAchR activity ( 33 , 34 , 37 ). We found that the fem-1 mutants were significantly ( P < 0.001) more sensitive to aldicarb but not to levamisole ( P = 0.34) compared to wild-type worms ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High-throughput chemical screening, genetic screening, and behavioral assays can be easily achieved using this model system (Naranjo-Galindo et al 2022 ). A recent study evaluated the morphological and behavioral endpoints of C. elegans in the context of reported AOP of neurodegenerative disorders and demonstrated the homology of human genes and associated proteins in the cholinergic and dopaminergic signaling system (Sammi et al 2022 ). Also, an EFSA study conducted in 2018 showed that this model organism can be used as an alternative tool for ANT and MoA (Masjosthusmann et al 2018 ).…”
Section: Nams and Neurotoxicity Assessmentmentioning
confidence: 99%